An Empirical Analysis of Mexican Merger Policy - Avalos, Marcos (The World Bank, 2008)
A newly created dataset including 239 decisions made by the Mexican Federal Competition Commission on horizontal mergers between 1997 and 2001 is used to estimate the different factors affecting the Commission's resolution. The paper approximates the decision making process using two different discrete choice models. The results indicate that, contrary to the Commission's objective, the presence of efficiency gains increases the probability of a case being issued. The findings also show that factors different from the ones explicitly mentioned by the Commission have a significant effect on the Commission's final decision. In particular, the presence of a foreign company among the would-be merger firms significantly increases the likelihood of observing an allowed merger